Introducing all‐polyamide composite coated fabrics: A method to produce fully recyclable single‐polymer composite coated fabrics. Issue 7 (2nd September 2015) - Jabbari, Mostafa; Skrifvars, Mikael; Åkesson, Dan; Taherzadeh, Mohammad J.
ABSTRACT: Novel all‐polyamide composite (APC) has been developed to replace traditional coated fabrics with good interfacial adhesion and enhanced recyclability. The composite is fully recyclable since it contains no other materials except polyamide. APC was prepared by partially dissolving a polyamide fabric by treatment with a film‐forming polyamide solution. The effect of the polyamide solution concentration and gelling time on tensile and viscoelastic properties of APCs was investigated to explore the optimum processing parameters for balancing the good interfacial adhesion. The composite properties were studied by dynamic mechanical thermal analysis (DMTA), tensile testing and scanning electron microscopy (SEM). The results showed a good adhesion between the coating and the fabric. A new method was introduced to convert a low value added textile waste to a high value‐added product. The composite is tunable, in terms of having a dense or a porous top‐layer depending on the end‐use requirements. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 42829. Abstract :